Chapter 8 Learning of written language A study focused on a group of deaf and hard-of-hearing students in Haiti - LAINY, Rochambeau (Taylor & Francis, 2023)
The deaf and hard-of-hearing sometimes experience constraints that differ from those of hearing people; plus, when this physiological state (deafness) coincides with other disorders, learning to write becomes exceptionally difficult. The main interest of this chapter includes the strategies that hard-of-hearing and deaf (non-hearing) children devise to learn to write and how they use writing in the development of knowledge in the Haitian context. It is a matter of understanding how these children manage to learn to read and write, and of analyzing impacts of judgements on their school performances. As deafness, seen in particular from the angle of sensorimotor disorder is described as phenomenon that impose social specific limitations on children, this chapter is to study the impacts of pedagogical practices on the learning process of written language. The deafness as a characteristic of a community of people that are culturally and linguistically different community, is notably studied.